Adding deltoid ligament repair in ankle fracture treatment: Is it necessary? A systematic review. Issue 6 (December 2019) - Dabash, Sherif; Elabd, Ahmed; Potter, Eric; Fernandez, Isaac; Gerzina, Chris; Thabet, Ahmed M.; McGarvey, William; Abdelgawad, Amr
Highlights: The most common mechanisms of injury to deltoid ligament are pronation-abduction, pronation-external rotation (PER), and supination-external rotation (SER). Controversy surrounds the treatment of DL rupture in literature. The purpose of this article is to review the literature of DL repair and establish a clear indication for operative intervention. Abstract: Background: Deltoid ligament injuries are typically caused by supination-external rotation or pronation injury. Numerous ligament reconstruction techniques have been proposed; however, clear indications for operative repair have not yet been well established in the literature. Methods: We reviewed primary research articles comparing ORIF treatment for ankle fracture with versus without deltoid ligament repair. Results: Five studies were identified with a total of 281 patients. 137 patients underwent ORIF with deltoid repair, while 144 patients underwent ORIF without deltoid ligament repair. Clinical, radiographic, and functional outcomes, as well as complications were considered. The average follow-up was 31 months (range, 5–120). Conclusions: Current literature does not provide clear indication for repair of the deltoid ligament at the time of ankle fracture repair. There may be some advantages of adding deltoid ligament repair for patients with high fibular fractures or in patients with concomitant syndesmotic fixation. Level of clinical evidence: III.